2013
DOI: 10.1016/j.molcel.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The Aurora B Kinase and the Polycomb Protein Ring1B Combine to Regulate Active Promoters in Quiescent Lymphocytes

Abstract: Reversible cellular quiescence is critical for developmental processes in metazoan organisms and is characterized by a reduction in cell size and transcriptional activity. We show that the Aurora B kinase and the polycomb protein Ring1B have essential roles in regulating transcriptionally active genes in quiescent lymphocytes. Ring1B and Aurora B bind to a wide range of active promoters in resting B and T cells. Conditional knockout of either protein results in reduced transcription and binding of RNA Pol II t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 34 publications
8
100
2
1
Order By: Relevance
“…6E). Although this seems surprising given that Ring1B and H2A ubiquitination are generally associated with gene silencing, gene activation by Ring1B has been reported in quiescent lymphocytes (40). It should be noted, however, that the activating effect of PRC1 becomes detectable only after BAP1 depletion in our experiments.…”
Section: Discussioncontrasting
confidence: 69%
“…6E). Although this seems surprising given that Ring1B and H2A ubiquitination are generally associated with gene silencing, gene activation by Ring1B has been reported in quiescent lymphocytes (40). It should be noted, however, that the activating effect of PRC1 becomes detectable only after BAP1 depletion in our experiments.…”
Section: Discussioncontrasting
confidence: 69%
“…We have recently shown that transcriptional activity persists during differentiation or physiological stress, despite increased genic H3K27me3-enrichment [33,[55][56][57]. Conversely, PRC1 was suggested to be required for gene expression in specific settings [58][59][60][61][62], illustrating the complexity of the functional interaction between PRC1 and H3K27me3 in the context of transcriptional regulation. H3K27me3-decoration may provide local epigenetic marking that directs lineage-dependent coordination of DNA transcription, replication.…”
Section: Discussionmentioning
confidence: 99%
“…H3S28P is mediated by human MSK1 and is associated with RNAPII phosphorylation at CTD S5 at the C-FOS and Α-GLOBIN promoters (Drobic et al, 2010;Keum et al, 2013;Lau and Cheung, 2011). Human Aurora B kinase phosphorylates H3S10 and H3S28 and plays significant roles during mitosis (Crosio et al, 2002;Frangini et al, 2013). Genome-wide analysis further shows that Aurora B kinase phosphorylates histone H3S28 and is associated with RNAPII phosphorylation at CTD S5 at the active gene promoters of resting human B-cells, preventing H2A ubiquitylation by the polycomb protein RING1B (Frangini et al, 2013).…”
Section: Rnapii Ctd and Histone Phosphorylationmentioning
confidence: 98%
“…Human Aurora B kinase phosphorylates H3S10 and H3S28 and plays significant roles during mitosis (Crosio et al, 2002;Frangini et al, 2013). Genome-wide analysis further shows that Aurora B kinase phosphorylates histone H3S28 and is associated with RNAPII phosphorylation at CTD S5 at the active gene promoters of resting human B-cells, preventing H2A ubiquitylation by the polycomb protein RING1B (Frangini et al, 2013). In Drosophila, JIL-1 kinase, a homologue to mammalian MSK1, phosphorylates both H3S10 and H3S28 in interphase cells and regulates transcription elongation by associating with S2-phosphorylated RNAPII at the Hsp70 (heat shock protein 70) gene (Ivaldi et al, 2007;Wang et al, 2013).…”
Section: Rnapii Ctd and Histone Phosphorylationmentioning
confidence: 99%